Demographic genetics of the endangered Amiata donkey breed [Tuscany] - Cecchi, F; Ciampolini, R; Ciani, E; Matteoli, B; Mazzanti, E; Tancredi, M; Presciuttini, S (Italian journal of animal science, 2006)
The demogenetic structure of the Amiata donkey, an endangered breed from Central Italy, was investigated using information from pedigrees. Genealogical data of 602 donkeys reared in Tuscany were recorded in a database and analysed by the computer package ENDOG. Population size increased from 89 subjects in 1995 to 503 (129 males and 374 females) in 2005. Animals were distributed among 152 herds, but the effective number of herds was 21, suggesting that a small number of herds provided stallions for the entire breed. The maximum number of traced generations was 4, the mean maximum generation was 1.14, the mean complete generation was 0.53, and the mean equivalent generation was 0.78. The average relatedness coefficient (AR) in the 503 alive animals was 0.94%, while the mean F was 0.29%, so the effective population size was 172.41. Among 24 animals with a 4-generation history, 3 (12.5%) were 25% inbred. Although the incompleteness of genealogical information did not permit accurate inference of the current values of population genetic parameters, the present work represents a first step towards an efficient management of the breed L'asino dell'Amiata è una razza autoctona toscana in pericolo di estinzione. Attraverso l'analisi delle informazioni derivanti dalle schede di registrazione anagrafica è stata analizzata la struttura demografica della razza. I dati genealogici di 602 asini allevati nel comprensorio della Toscana sono stati archiviati in un database informatizzato e analizzati mediante il programma ENDOG. Gli effettivi numerici della popolazione sono aumentati da 89 soggetti nel 1995 a 503 (129 maschi e 374 femmine) nel 2005. I capi erano distribuiti in 152 allevamenti, sebbene il numero di allevamenti effettivi fosse pari a 21, ovvero solo un ristretto numero di allevamenti ha fornito gli stalloni impiegati per l'intera popolazione. Il numero massimo di generazioni era pari a 4, il numero mediato tra tutti gli individui era 1,14, il numero medio di generazioni complete era 0,53 e il numero medio di generazioni equivalenti era 0,71. La parentela media tra i 503 animali vivi è risultata di 0,94%, mentre la consanguineità media è risultata pari a 0,29%, con un numero effettivo di popolazione pari a 172,21. Dei 24 animali con informazioni disponibili su quattro generazioni, 3 (12,5%) presentavano un coefficiente di inbreeding pari al 25%. Sebbene l'incompletezza delle informazioni genealogiche non abbia permesso una stima accurata dei valori attuali per i principali parametri genetici, il presente lavoro costituisce un primo passo nella direzione di una gestione più efficiente e consapevole della razza